MANFAAT BUAH NAGA SEBAGAI ANTIOKSIDAN DALAM SEDIAAN GUMMY KEPADA MASYARAKAT PURWASARI, KARAWANG - Eko Sri Wahyuningsih; Neni Sri Gunarti; Lia Fikayuniar; Putri Agustina (JURNAL PENGABDIAN MANDIRI, 2025)
Free radicals can be caused by environmental factors such as air pollution, excessive exposure to UV rays, temperature, chemicals, and due to lack of nutritional intake in the body. If exposed to excessive free radicals, there will be a connection between free radical molecules and endogenous antioxidants. Antioxidants are beneficial for humans as they prevent aging, strengthen the immune system, protect the nervous system, and can improve eye health. Red dragon fruit (Hylocereus polyrhizus) is a type of dragon fruit that has many benefits, the benefits of red dragon fruit include being an antioxidant, because red dragon fruit contains bioactive antioxidant substances (ascorbic acid, beta-carotene and anthocyanins). The method in this community service is a strategy in implementing this community service activity, explaining or providing an understanding related to antioxidants, free radicals, their effects on the human body, and the importance of antioxidants in fighting free radicals in the body. Next, information regarding red dragon fruit, which is very useful as a free radical scavenger, is provided. The conclusion in this community service activity is that the community service activities that have been carried out, all the Karawang residents who were present in Kp. Nagasari, ds. Karangsari, Kec. Purwasari, Karawang Regency, West Java who attended this activity have understood and comprehended the importance of utilizing dragon fruit skin as an antioxidant and community service has run smoothly.